Effect of cool dialysate on vital signs, comfort and adequacy - Seyed Reza Borzou; Fateme Farghadani; Khodayar Oshvandi; Mahmood Gholyaf; Hosein Mahjub (Journal of Holistic Nursing and Midwifery)
Abstract Introduction: Cool dialysate solution is an important factor in maintenance of cardio–vascular stability in hemodialysis patients. Objective: This study aimed to determine the effect of dialysate temperature on vital signs, comfort and adequacy of dialysis in hemodialysis patients. Methods: This study is a clinical trial conducted on 30 hemodialysis patients hospitalized in hemodialysis ward of one of Hamedan hospitals. Eligible patients were selected by simple sampling method and then three sessions of interventions were done. Patients were dialyzed at 37º C in first level and 35ºC and 36ºC in the second and third levels during three sessions. Patients blood pressure and pulse rate were controlled before and after dialysis and in the first, second and third hour during dialysis. But patients body temperature was controlled before and after each session. In the third session, patients blood samples were collected before and after dialysis to assess the KT / V. At the end of session, patients were assessed for comfort using visual criteria. For data analysis repeated measurement, variance analysis and Tukey test were used. P value less than 0.05 was considered statistically significant. Results: Research findings showed that although with reduction of dialysate temperature, systolic blood pressure of patients slightly increased, but this increase was not statistically significant. Patients' pulse reduced significantly by decreasing. Patients were more comfortable at lower temperature. And only 6.7% of patients preferred 37C º temperature. Dialysate temperature did not matter to 20% of patients while the rest preferred cool dialysate. Patients KT/V showed a significant increase at 35C º temperature compared to 36ºC and 37ºC. Conclusion: According to the research findings although reduced dialysate temperature may not be useful for all patients but considering its benefits, it is recommended considering patient s condition and comfort level, dialysate with lower temperature be usedAccording to the research findings although reduced dialysate temperature may not be useful for all patients but considering its benefits, it is recommended considering patient s condition and comfort level, dialysate with lower temperature be used.